KOORDINASI DALAM PROGRAM KAMPUNG KB DI KOTA PEKANBARU - Fauziah Riska Rahmeina; Nur Laila Meilani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Coordination is an important role in an organization to archive the desired goal. Kampung KB Program as an implementation of program related to partners of BKKBN Riau Province. This research aims to obtain a description the coordination among BKKBN Riau Province, Population control and family planning office of pekanbaru city, and field line in Kampung KB implementation of Pekanbaru city and to identify the factors that affect the coordination of Kampung KB program of Pekanbaru city.Blade analysis in this study comes from the book writen by Malayu Hasibuan involving that coordination includes cooperation, communication, division of task and discipline. This research uses qualitative-descriptive method. In data collection, writer uses interviewing technique, observation, documentation and questionnaires. Using purposive sampling as an information source and interactive model as data analysis technique.The result of the research indicate that the coordination that has been done by BKKBN Riau Province and The controlling service of population and family planning of Pekanbaru city has been running optimally but the coordination to cross sectoral and the regional tool not yet optimal. Coordination is influenced by several factors : budget and advocacy to cross-sectoral.Keywords: Socialization, Rusunawa, Program